Application of the ATN classification scheme in a population without dementia: Findings from the EPAD cohort. Issue 7 (3rd April 2021) - Ingala, Silvia; De Boer, Casper; Masselink, Larissa A; Vergari, Ilaria; Lorenzini, Luigi; Blennow, Kaj; Chételat, Gaël; Di Perri, Carol; Ewers, Michael; van der Flier, Wiesje M; Fox, Nick C; Gispert, Juan Domingo; et al.
Abstract: Background: We classified non‐demented European Prevention of Alzheimer's Dementia (EPAD) participants through the amyloid/tau/neurodegeneration (ATN) scheme and assessed their neuropsychological and imaging profiles. Materials and methods: From 1500 EPAD participants, 312 were excluded. Cerebrospinal fluid cut‐offs of 1000 pg/mL for amyloid beta (Aß)1‐42 and 27 pg/mL for p‐tau181 were validated using Gaussian mixture models. Given strong correlation of p‐tau and t‐tau (R 2 = 0.98, P < 0.001), neurodegeneration was defined by age‐adjusted hippocampal volume. Multinomial regressions were used to test whether neuropsychological tests and regional brain volumes could distinguish ATN stages. Results: Age was 65 ± 7 years, with 58% females and 38% apolipoprotein E (APOE) ε4 carriers; 57.1% were A–T–N–, 32.5% were in the Alzheimer's disease (AD) continuum, and 10.4% suspected non‐Alzheimer's pathology. Age and cerebrovascular burden progressed with biomarker positivity ( P < 0.001). Cognitive dysfunction appeared with T+. Paradoxically higher regional gray matter volumes were observed in A+T–N– compared to A–T–N– ( P < 0.001). Discussion: In non‐demented individuals along the AD continuum, p‐tau drives cognitive dysfunction. Memory and language domains are affected in the earliest stages.